Organizational Silence: An Assessment from the Perspective of University Librarians - Işık, Demet; Yıldırım, Banu Fulya (Information World, 2025)
Organizational silence, a significant idea that influences an organization’s operations, activities, and dynamics, is examined in this study. Situations where people or groups avoid or keep quiet about sharing their ideas, opinions, and suggestions - particularly regarding the challenges, issues, or change processes encountered within the organization - are referred to as organizational silence. Organizational silence in this situation can have a significant impact on both individuals and the organization’s overall operation. This study introduces the idea of organizational silence, highlights its causes, and examines its dimensions in university libraries, which represent a particular kind of organization. This study aims to identify the factors that lead university librarians to choose to remain silent in the library and investigate whether the impact levels of these factors vary depending on certain demographic variables. The study employed one of the quantitative research approaches, the descriptive method. A total of 171 librarians employed by state universities in Ankara, İstanbul, and İzmir libraries participated in the study. A personal information form and the “reasons for silence scale” (Çakıcı, 2008) were used to gather the research data. The reasons for organizational silence were evaluated in terms of five factors: “administrative and organizational reasons”, “work-related fears”, “lack of experience”, “fear of isolation” and “fear of damaging relationships”. The t-test and one-way analysis of variance, or ANOVA, were employed in the data analysis process. The results regarding the effect levels of the factors that cause university librarians to prefer to remain silent show that high values are reached in the dimension of fear of damaging relationships. Furthermore, the findings indicate that there is a statistically significant difference in the two factors of the reasons for silence in terms of age and city variables. Statistically significant differences were found according to the education level variable. University librarians’ opinions on the reasons behind organizational silence were revealed by the study’s findings. Additionally, the study contributes to the creation of awareness regarding organizational silence in libraries.
Keywords: Organizational silence; organizational behavior; employee silence; university libraries; librarians